The impact on academic staff of the collaboration between a pathway provider and its partner university: An Australian case study. - Kaktiņš, Louise (Journal of University Teaching and Learning Practice, 2018)
New educational models such as those involving a third party educational provider linked with an official university for purposes of providing a bridge (a pathway program) into a mainstream university degree, particularly for international students, have become part of the higher education landscape capitalising on the international demand for tertiary qualifications from Australia and other English-language-based universities. The perceptions of teachers employed in one such pathway program are the focus of this current paper – a research area that to date has been understudied. Such data are of great value in furnishing an in-depth view of the challenges involved in an educational model that is highly commercialised and the impacts it has on teaching and learning, especially on academic identity in terms of the specific key relationships – between teachers and third party provider, between teachers and partner university, between teachers and international students. Some of the more concerning issues revolve around the extent to which market imperatives impinge on pedagogical concerns, on teachers’ professional commitment to their vocation, on international students’ capacity to acquire an authentic tertiary education that supports rather than detracts their transition to mainstream university, and on whether such educational models can be genuinely sustainable long term.